Early-Life Lung and Gut Microbiota Development and Respiratory Syncytial Virus Infection - Yagi, Kazuma; Asai, Nobuhiro; Huffnagle, Gary B.; Lukacs, Nicholas W.; Fonseca, Wendy (Frontiers in Immunology, 2022)
Several environmental factors can influence the development and establishment of the early-life microbiota. For example, exposure to different environmental factors from birth to childhood will shape the lung and gut microbiota and the development of the immune system, which will impact respiratory tract infection and widespread disease occurrence during infancy and later in life. Respiratory syncytial virus (RSV) infects most infants by the age of two and is the primary cause of bronchiolitis in children worldwide. Approximately a third of infants hospitalized with bronchiolitis develop asthma later in life. However, it is unclear what factors increase susceptibility to severe RSV-bronchiolitis and the subsequent asthma development. In recent years, the role of the gut and lung microbiota in airway diseases has received increased interest, and more studies have focused on this field. Different epidemiological studies and experimental animal models have associated early-life gut microbiota dysbiosis with an increased risk of lung disease later in life. This work will review published evidence that correlated environmental factors that affect the early-life microbiota composition and their role in developing severe RSV infection.